Rapid diagnostic value of next-generation sequencing-based technologies in childhood pneumonia - Chen, Yanfei; Zhu, Xiaoli; Fang, Fang; Ma, Kaihui; Zhang, Yanli; Liu, Hongxia (Frontiers in Pediatrics, 2026)
BackgroundThis study evaluates the diagnostic efficacy of next-generation sequencing (NGS) in pediatric patients with suspected pneumonia and unidentified etiologies.ObjectiveThis retrospective study encompassed pediatric patients with suspected pneumonia, spanning the period from January 2022 to December 2023. Nasal swabs and blood samples were collected for a comprehensive diagnostic panel, including NGS, blood culture, complete blood count, and serum biomarkers.MethodsRoutine diagnostic tests were compared with NGS for turnaround time and diagnostic accuracy. Patients were categorized based on clinical diagnosis into non-pneumonia and pneumonia groups. Logistic regression analysis was performed to identify independent predictors of pneumonia.ResultsNGS provided results within 24 h, significantly faster than conventional bacterial cultures (3–5 days). The positivity rate for pathogen identification increased from 55.3% with traditional methods to 86.2% with NGS (p < 0.05). Serum levels of procalcitonin, creatinine, and C-reactive protein were elevated in pneumonia patients, while albumin levels were decreased. Logistic regression identified C-reactive protein and albumin as independent predictors of pneumonia. The area under the receiver operating characteristic curve for NGS was superior to conventional methods and serum biomarkers alone or in combination.ConclusionNGS is a promising tool for rapid and accurate etiologic diagnosis of pneumonia in children. The combination of NGS with albumin levels may serve as an effective screening strategy, potentially enhancing clinical management through earlier intervention and targeted therapy. Further validation in larger cohorts is warranted to establish the clinical utility of this approach.